KINJENG TRUNG GENDING KERAMAT DARI DUKUH MAJAPAHIT - Rabimin Rabimin (Institut Seni Indonesia Surakarta, 2010)
This writing gives an information on gending (melody) Kinjeng Trung thought to be sacred by the people of Dukuh Majapahit (Sambungmacan – Sragen) and its surroundings. When the invited guests from Dukuh Majapahit attending a banquet are not welcome with the presentation of gending Kinjeng Trung, the one who holds a banquet will get an accident or feel ashamed and will not feel safe because there will be an unnatural circumstance such as the food cooked is not done, dominated by an evil spirit, getting ill suddenly, and so on. Kinjeng Trung gending has been known in Dukuh Majapahit and its surroundings since about the 15th century. In addition to being a gending for accompanying Tayub and Badhutan, the main function of Kinjeng Trung gending is to render honors so that it is everlasting. Recently the gending has been making rapid progress in cakepan, the instruments, garap and function. This writing gives some information on problems such as: historical background, notation of gerongan and sindenan. This writing aims to help the reader to understand the content and practice. Key words : kinjeng trung, sacred, Majapahit